Significados atribuídos às práticas na atenção primária à saúde por estudantes de medicina - Santos, Everson Vagner de Lucena (2016)
Medical training has been undergoing significant changes based on the new national curricular guidelines for the medical course, with emphasis on the insertion of the medical student in several scenarios that stimulate critical and reflexive formation, focusing on Primary Health Care. Considering this is a scenario of meaningful learning that fosters personal relationships, this research aimed at understanding the meanings attribuited to primary health care practices by medical students. This study was a qualitative research conducted at the Integrated Faculties of Patos, using the in-depth interview technique with medical students attending between the 1st and the 4th semester of course. The composition of the study population took into consideration a research participation invitation and a plurality of criteria, such as gender, age, place of origin, semester in progress, scholarship/financing, medical kinship, and previous graduation degree, totalizing 9 students who attended the theoretical saturation criterion. The interviews were conducted from December2015 to February 2016 and continually recorded in digital audio, lasting from 25 to 90 minutes. The research was approved by the Ethics Committee of the Catholic University of Santos and the interviews were carried out after clarification and signing of the Free and Informed Consent Form. The analytical interpretation was developed based on stages such as pre-analysis, exploitation of the material, treatment of results obtained, and interpretation. The selection of analytical categories was performed by means of anchoring the reading and the substrate, extracted from the empirical data, producing an understanding of the meaning attributed to contradictions, diversities, and tensions that were guided by the Theory of Meaning ful Learning developed by David Ausubel. The empirical data of the study identified the understanding of meanings attributed to the teaching-learning process in Primary Health Care and its practices for the professional dimension and within the scope of the individual's singularity. The findings showed the meanings in different scopes (teaching-learning, professional and personal training) are in agreement with the postulates of the egress profile published in the national curricular guidelines for medical courses, stating the importance of the insertion of the student in spaces of Primary Health Care of the Brazilian National Health System since the beginning of the course, because it is significant for the egress profile and also an indication of a change in medical training and practices in Brazil.